Summaries of cases dealt with by the almoner - Brimmell, Maud E.
1903-09-28 1903 1900s 5 pages 5 wks. of whom he had little personal knowledge. With many misgivings he allowed me to consult the C.O.S. declining to do so himself. Woman was living in very bad surroundings & enquiries proved that there was no prospect of a livelihood there. She was sent to a country laundry, interviewed & accepted on trial. Many difficulties as to children were met & dealt with - but in the end association proved too strong - her courage failed her & the habit of drink grew [on the woman] & the case had to be given up. The clergyman was satisfied that the Widow's Gift would have been wrongly given, & realised how carefully & patiently the case had been dealt with. 10. 15 mths. G.W. w. 36. 4 young ch. Guardians take two ch. Mother is training as cook till it comes to light that she is addicted to drink. Material help ceases, but strong personal interest is not relaxed until a situation is found where her weakness is known & guarded against. She is now a trusted servant - has regained her self respect, & has a comfortable home for herself & two children 11. M.E. w. 41. see c.p. 12. J.A. s. 21. see c.p. 378/IMSW/A/1/2/44